THE EFFECT OF LIGHTING LENGTH WITH LED AND FLUORESCENT LAMPS COMBINATION ON THE GROWTH AND PRODUCT OF PAKCOY (Brassica rapa L.) WITH WICK SYSTEM HYDROPONICS - Lindawati, Yesi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This research aimed to find out the lighting length of the combination LED and fluorescent lamps combined,suitable to growpakcoy (Brassica rapa L.)withwick systemhydroponics. The research used five treatments: sunlighting as a control (P0), and artificial lighting of 36-watt LED combined with 42-watt fluorescent lamps. Sunlighting represented a conventional cultivation, with normal lighting period (Â±12 hours per day), while theartificial lighting consisted of four different lighting lengths per day: 8 hours (P1), 12 hours (P2), 16 hours (P3)and 20 hours (P4). The artificial lighting experiments were placed in boxes as the growth chambers, while theregular sunlighting treatmentwas placed inan outdoorminigreenhouse. Each treatment consisted of four plants,so there were 20 plants in total. The results showed that 20-hour treatment of 36-watt LED lamp plus 42-wattfluorescent lighting (P4) was the best among the other artificial lighting treatments, but still less optimal ascompared to the treatment of natural sun lighting (P0). The plants grew in treatmentP4 still showed etiolating,indicating possibility of using higher power than 36-watt LED lamp and 42-watt fluorescent, although the lengthof lighting reached 20 hours. Yet, in termof quality, the mineral/ash content of all treated plants was notmuchdifferent.Keyword : LED lamp, fluorescent lamp, lighting, pakcoy,wick systemhydroponics.